The material culture of writing - Alexis, Cydney; Rule, Hannah J., 1981- (Utah State University Press, 2022)
"This book opens up avenues for understanding writing through scholarship in material culture studies. Contributors each interrogate an object, set of objects, or writing environment to reveal the sociomaterial contexts from which writing emerges. Close study of such artifacts offers up the potential for inquiry into writing artifacts and environments"--